Strategic Analysis of the Automation of Container Port Terminals through BOT (Business Observation Tool) - Alberto Camarero Orive; José Ignacio Parra Santiago; María Magdalena Esteban-Infantes Corral; Nicoletta González-Cancelas (Logistics)
The port system is immersed in a process of digital transformation towards the concept of Ports 4.0, under the new regulatory and connectivity requirements that are expected of them. As a result of the changes that the industrial revolution 4.0 is imposing, based on new information technologies and the change of energy model, the electrification of modes of transport from alternative energies and the total digitalization of the processes is occurring. This conversion to digital, intelligent, and green ports requires the implementation of the new technologies offered by the market. The inclusion of these enabling tools has allowed the development of automated terminals under a functional approach. This article aims to offer the responsible entities a new methodology (BOT) that allows them to successfully undertake the automation of terminals, taking into account the reality of the conditions of the environment in which they are developed. By quantifying the factors that facilitate or impede implementation, it will be possible to determine the strategy to be followed and the necessary measures to be adopted in the project; constituting, therefore, a novel management and planning tool.